Prevalence and characterization of IncQ1α-mediated multi-drug resistance in Proteus mirabilis Isolated from pigs in Kunming, Yunnan, China - Hongmei Liu; Hongmei Liu; Hongmei Liu; Na Xia; Fanan Suksawat; Bundit Tengjaroenkul; Yue Hu; Xiaofeng Zhou; Xiaojiang Li; Cuiqin Huang; Yinli Bao; Qiong Wu; et al. (Frontiers in Microbiology)
BackgroundProteus mirabilis is a conditionally pathogenic bacterium that is inherently resistant to polymyxin and tigecycline, largely due to antibiotic resistance genes (ARGs). These ARGs can be horizontally transferred to other bacteria, raising concerns about the Inc plasmid-mediated ARG transmission from Proteus mirabilis, which poses a serious public health threat. This study aims to investigate the presence of Inc plasmid types in pig-derived Proteus mirabilis in Kunming, Yunnan, China.MethodsFecal samples were collected from pig farms across six districts of Kunming (Luquan, Jinning, Yiliang, Anning, Songming, and Xundian) from 2022 to 2023. Proteus mirabilis isolates were identified using IDS and 16S rRNA gene sequencing. Then, positive strains underwent antimicrobial susceptibility testing and incompatibility plasmid typing. Multi-drug-resistant isolates with positive incompatibility plasmid genes were selected for whole-genome sequencing. Resistance and Inc group data were then isolated and compared with 126 complete genome sequences from public databases. Whole-genome multi-locus sequence typing, resistance group analysis, genomic island prediction, and plasmid structural gene analysis were performed.ResultsA total of 30 isolates were obtained from 230 samples, yielding a prevalence of 13.04%. All isolates exhibited multi-drug resistance, with 100% resistance to cotrimoxazole, erythromycin, penicillin G, chloramphenicol, ampicillin, and streptomycin. Among these, 15 isolates tested positive for the IncQ1α plasmid repC gene. The two most multi-drug-resistant and repC-positive strains, NO. 15 and 21, were sequenced to compare genomic features on Inc groups and ARGs with public data. Genome analysis revealed that the repC gene was primarily associated with IncQ1α, with structural genes from other F-type plasmids (TraV, TraU, TraN, TraL, TraK, TraI, TraH, TraG, TraF, TraE/GumN, and TraA) also present. Strain NO. 15 carried 33 ARGs, and strain NO. 21 carried 38 ARGs, conferring resistance to tetracyclines, fluoroquinolones, aminoglycosides, sulfonamides, peptides, chloramphenicol, cephalosporins, lincomycins, macrolides, and 2-aminopyrimidines.ConclusionThe repC gene is primarily associated with IncQ1α, with structural genes from other F-type plasmids. A comparison with 126 public genome datasets confirmed this association.